A MSFD complementary approach for the assessment of pressures, knowledge and data gaps in Southern European Seas: The PERSEUS experience. Issue 1 (15th June 2015) - Crise, A.; Kaberi, H.; Ruiz, J.; Zatsepin, A.; Arashkevich, E.; Giani, M.; Karageorgis, A.P.; Prieto, L.; Pantazi, M.; Gonzalez-Fernandez, D.; Ribera d'Alcalà, M.; Tornero, V.; et al.
Highlights: A complementary approach to MSFD gaps is proposed for Southern European Seas. Multidisciplinary large effort that represents the common view of SES marine community. Research priorities are summarized, descriptor by descriptor, in the synthesis tables. The knowledge and data gaps differ in open sea and coastal hot spots. Limited workable insight for biodiversity, food web, marine litter, underwater noise. Abstract: PERSEUS project aims to identify the most relevant pressures exerted on the ecosystems of the Southern European Seas (SES), highlighting knowledge and data gaps that endanger the achievement of SES Good Environmental Status (GES) as mandated by the Marine Strategy Framework Directive (MSFD). A complementary approach has been adopted, by a meta-analysis of existing literature on pressure/impact/knowledge gaps summarized in tables related to the MSFD descriptors, discriminating open waters from coastal areas. A comparative assessment of the Initial Assessments (IAs) for five SES countries has been also independently performed. The comparison between meta-analysis results and IAs shows similarities for coastal areas only. Major knowledge gaps have been detected for the biodiversity, marine food web, marine litter and underwater noise descriptors. The meta-analysis also allowed the identification of additional research themes targeting research topics that are requested to the achievement of GES.